Gold investment account in Malaysia - Ab Majid, Hafizi; Syed Jaafar Alhabshi, Syed Musa; Janor, Hawati; Niaz Ahmad, Mohd Naseem; Kamarudin, Mohd Faizal (Jabatan Syariah, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2016)
Gold investment in Malaysia offers a rewarding and secure asset class for public through two different methods, physical gold or gold investment account (GIA). This research provides a comprehensive discussion on the GIA in Malaysia, its characteristics, structure and contemporary applications. GIA allows investor to make deposits when gold prices are low and withdraw the funds at profit when the gold price rises. The shariah compliance issues are also discussed. This research follows qualitative research method. Semi-structured interviews were conducted with the banks representatives to gain the information on GIA in Malaysia. Since studies on gold investment account have been scarce compared to other types of investment, this study contributes to the literature and serves as good practices of investor’s guideline.